Peripheral killer cells do not differentiate between asthma patients with or without fixed airway obstruction - Tubby, Carolyn; Negm, Ola H.; Harrison, Timothy W.; Tighe, Patrick J.; Todd, Ian; Fairclough, Lucy C. (Taylor & Francis, 2016)
Objective: The three main types of killer cells – CD8+ T cells, NK cells and NKT cells – have been linked to asthma and chronic obstructive pulmonary disease (COPD). However, their role in a small subset of asthma patients displaying fixed airway obstruction (FAO), similar to that seen in COPD, has not been explored. The objective of the present study was to investigate killer cell numbers, phenotype and function in peripheral blood from asthma patients with FAO, asthma patients without FAO, and healthy individuals. Methods: Peripheral CD8+ T cells (CD8+CD3+CD56−), NK cells (CD56+CD3−) and NKT-like cells (CD56+CD3+) of 14 asthma patients with FAO (post-bronchodilator FEV/FVC <0.7, despite clinician-optimised treatment), 7 asthma patients without FAO (post-bronchodilator FEV/FVC ≥0.7), and 9 healthy individuals were studied. Results: No significant differences were seen between the number, receptor expression, MAPK signalling molecule expression, cytotoxic mediator expression, and functional cytotoxicity of peripheral killer cells from asthma patients with FAO, asthma patients without FAO and healthy individuals. Conclusions: Peripheral killer cell numbers or functions do not differentiate between asthma patients with or without fixed airway obstruction.